Analysis on the Key Factors of the Network Separation in China in the Era of Telecommunications 4.0 - Yu Yang; Luona Song; Tingjie Lv; Xia Chen (International Telecommunications Society (ITS), 2017)
The era of telecommunications 4.0 is a challenge to regulators and operators insofar as external environment, technology (such as SDN and NFV), and consumers' requirements have changed. This paper's main objective is to introduce and discuss several issues around the implementation of network separation as a regulatory remedy. The paper discusses network separation practice in several countries (including Sweden, the UK, Italy, Ireland, New Zealand, Australia and Singapore) and summarizes their advantages, disadvantages, process as well as effects. All findings are rendered in tabular form according to different separation modes which are accounting separation, functional separation, operational separation and ownership separation. Moreover, this paper discusses the main elements of a possible test for the adequacy of network separation. A sequential decision tree procedure with three questions is proposed: (1) Is there significant market power in China in the era of telecommunications 4.0? (2) Are there little vertical complementarities between services along the supply chain? (3) Is network separation a better regulatory tool than any other alternative remedy? By answering these three questions, the paper concludes that network separation is not suitable for China under the current situation.
Keywords: 330; telecommunications regulation; network separation; telecommunications 4.0